2005
DOI: 10.1332/0305573054325701
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative group dynamics: power, status and affect in interactive policy making

Abstract: English Many proponents of interactive policy making view citizen consultations as a ‘rational deliberation between equals’. Power, authority, rhetoric and emotions are considered to be obstructive factors. In this article it is argued that interactive policy settings are characterised by status and authority hierarchies and affect dynamics. First, two types of deliberative bodies are introduced: citizen forums and stakeholder committees. Next, eight possible power and emotion dynamics are distinguished, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…Other authors have disputed this equalization of participants' power as an ideal not always represented in deliberative practice. van Stokkom [62] emphasises that deliberative processes to inform policy do not always meet equality and rationality ideals. Behind the ideal of rational dialogue between equal participants the author finds an interplay of power and emotion dynamics that can aid or impede deliberation.…”
Section: Social Sustainability Stakeholder Participation and Dialoguementioning
confidence: 99%
“…Other authors have disputed this equalization of participants' power as an ideal not always represented in deliberative practice. van Stokkom [62] emphasises that deliberative processes to inform policy do not always meet equality and rationality ideals. Behind the ideal of rational dialogue between equal participants the author finds an interplay of power and emotion dynamics that can aid or impede deliberation.…”
Section: Social Sustainability Stakeholder Participation and Dialoguementioning
confidence: 99%
“…It suggested that bloggers engage in group discussions (Young, 1996;Sanders, 1997, Stokkom, 2003Mansbridge et al, 2006). In contrast, when the rational criticism was monopolized by the elite and ignored the masses, it demeaned the silent masses, which then became more assertive and confrontational.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of large-scale exercises, some aggregation or analysis by sub-group is likely to be necessary (Dienel, 1999;Orr, 2007). Crocker (2003) encourages attention to disagreement within the group including dissent which may not be verbalised as such, and placing emphasis in the report on the process as well as the outcome (Van Stokkom, 2005;White et al, 1999). Davies et al (2006) recommend that where there are unresolved disagreements, facilitators should produce a report giving an account of the reasoning behind the different conclusions.…”
Section: Analysis and Interpretationmentioning
confidence: 99%